Availability and Feasibility of Demand Side Management Projects in Egypt - Mohamed Gaber; Ahmed Mohamed Atef; Amr El Zawawi; Mohamed Salah (ARCHive-SR, 2019)
Demand Side Management (DSM) results in energy consumption reduction accompanied by lower cost according to the feasibility study for each project. In Egypt, DSM projects are scarce due to lack of good studies proving their underlining profitability. This paper studies the major types of DSM programs and their availability to be executed in Egypt. Tips to measure feasibility for these projects are given using the Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Payback Period (PP) and Discounted Payback Period(DPP). Different factors affecting the projects to study like the inflation factor and the discount rate are studied. This paper also investigates a new sustainable way for natural illumination called the sun tunnel. This method is presented with its different types: rigid and flexible as a case study.